Pseudo-Koebner in warts on tattoo. - Chieco, P. (European Journal of Pediatric Dermatology, 2019)
Warts mostly distributed (1, 2) on black lines (Fig. 1, 3 dermoscopy) of a tattoo performed two years earlier, with rare warts on normald skin (Fig. 2).